8. Römerquelle - Kunstwettbewerb 1988. - Galerie im Stadthaus, Klagenfurt; Neue Galerie der Stadt Linz; Wiener Secession, Wien; Galerie Stubenbastein, Wien (Wien : Römerquelle G.m.b.H., 1988)
Blittersdorff, Tassilo ; Weibel, Ulrich ; Deutsch, Johannes ; Poschauko, Hans Werner ; Schabhütti, Karin ; Schatz, Hubert ; Schabauer, Anton ; Scheucher, Hannes ; Blaas, Franz ; Kompatscher, Florin ; Mayrus, Wilfried ; Hutterer, Doris ; Wachter, Christian
8. Römerquelle - Kunstwettbewerb 1988, Galerie im Stadthaus, Klagenfurt, 8. - 29. Juni 1988 ; Neue Galerie der Stadt Linz, 7. Juli - 10. September 1988 ; Wiener Secession, Wien, 18. Oktober - 20. November 1988 ; Galerie Stubenbastei, 18 Oktober - 20. November 1988
boek